Effects of high-intensity interval training on antioxidant capacities - Vieira-Souza, Lucio Marques (2024)
High-intensity interval training (HIIT) is currently one of the most used methods mainly for the treatment of cardiovascular diseases, metabolic syndrome and obesity. The present study aimed to carry out an integrative review on the effect of the HIIT method on antioxidant capacities in humans. The search terms used were HIIT with the following keywords and correlates: oxidative stress, lipid peroxidation, antioxidant capacity, antioxidant enzymes and free radicals. Inclusion criteria were HIIT intervention studies on antioxidant capacity, original articles and available in full in English, Spanish and Portuguese. Studies that did not meet these criteria were excluded. A total of 27 articles were found, of which only 7 met the selection criteria. Of these, 6 studies (85%) investigated the effect of HIIT on antioxidant capacity found beneficial results in these parameters. On the other hand, in one of included studies, the damage was repaired after exercise and one (15%) did not obtain statistically significant reductions. In this review, scientific evidence points to the effects resulting from antioxidant capacity and HIIT, however, it is necessary to carry out further studies to analyze this relationship, as it is not yet well described in literature.